Bye bye Brasil: a modernização brasileira em tempos de ditadura militar síntese da miséria brasileira - Barbedo, Mariana (2010)
The present work aims the social-historical understanding of the Carlos Diegues movie Bye Bye Brazil, produced in 1979, from the axis of modernization in their historical particularities, namely a specific modernization which excluded the majority of accumulation processes. Thus the work verses about a period in which society has undergone changes in the life production - which led to changes in social relations, a fact that gives rise to key discussions that lead to understanding the paths taken by the Brazilian history. The research work looked toward the commencement of immanent analysis. We tried to capture the historicity of the film from the understanding of its interior, so that the issues which were addressed converged with our object (the modernization expression), such as the representation of Brazilian poverty, migration, national integration through the medias and the exacerbated glorification of foreign cultures. This analysis was marked by the understanding of determination and the social role of the movie. Thus, we tried to reflect on the universe of creation of the film, on the Carlos Diegues histories of life and artistics works, the production process of Bye Bye Brazil, the way it was seen, as well as its insertion in political and cultural debates that formed the environment in which the movie was produced. During the research it was found that Bye bye Brazil lends itself to laying bare the contradictions surrounding the modernization process under the aegis of the military dictatorship, which shows its intent: to put itself in favor of social awareness. We consider the understanding of these events, the social ground that inspired the author in which he sought to intervene, an important way to reflect and critically assess the Brazilian reality